Preparation-method-dependent morphological, band structural, microstructural, and photocatalytic properties of noble metal-GaNbO4 nanocomposites - Devi, Suman; Kelkar, Sarika A.; Kashid, Vikas; Salunke, Hemant G.; Gupta, Narendra M. (RSC Advances, 2013)
We report the distinct physicochemical and photophysical properties of gallium niobate photocatalysts (bandgap: similar to 3.1 eV), prepared by a solid-state (SS) reaction and sol-gel (SG) method and dispersed with a noble metal (similar to 0.5% of Pt, Au, or RuOx) cocatalyst. SG-GaNbO4 comprised smaller size particles (similar to 20-50 nm) and a larger surface area (similar to 160 m(2) g(-1)) compared to SS-GaNbO4 (particle size similar to 30-150 nm, surface area similar to 27 m(2) g(-1)). XRD patterns revealed a preparation-dependent variation in the relative intensity of prominent reflections. In TEM examination, SG samples exhibited small-range grain boundaries and heterogeneous metal/substrate interfacial contacts, while SS-GaNbO4 had long-range ordering. Laser-Raman and thermoluminescence investigations revealed that lattice distortion, defect-induced inter-bandgap charge trapping states, and the local environment around the metal/semiconductor interfaces may also depend on the preparation method. Metal-GaNbO4 nanocomposites showed no activity for the dissociation of pure water under UV (>250 nm) irradiation, despite the favourable conduction and valence band potentials. This was attributed to the sharp Ga and Nb d-levels in the narrow conduction band of GaNbO4, as confirmed by ab initio electronic structure calculation. These photocatalysts, however, showed good activity for semiconductor-mediated photo-dissociation of aqueous methanol to produce H-2; a cocatalyst-dependent activity trend, Pt > RuOx > Au, was observed. Doping of S at similar to 5% of the oxygen sites led to decreased photoactivity, ascribed to the presence of localized S 3p states just above the O 2p valence level. In conclusion, besides band characteristics, certain morphological and microstructural properties play a crucial role in the photoactivity of the metal/oxide nanocomposites.

Photophysical, bandstructural, and textural properties of o-FeNbO4 in relation to its cocatalyst-assisted photoactivity for water oxidation - Babu, Robin; Kelkar, Sarika A.; Kashid, Vikas; Achary, Srungarpu N.; Salunke, Hemant G.; Gupta, Narendra M. (RSC Advances, 2014)
In this study, a relationship between physicochemical, photophysical and photocatalytic properties of hydrothermally synthesized orthorhombic iron niobate (FeNbO4) is investigated. o-FeNbO4 displayed a multi-regime optical absorbance, which was ascribed to at least two distinct phenomena: (i) bandgap (similar to 3.4 eV) excitation giving rise to UV absorbance and (ii) energy transitions involving disorder-induced sub-bandgap donor or acceptor states leading to visible light absorbance. The preparation-dependent distortion in the crystal lattice and the existence of closely spaced inter-bandgap energy states were corroborated by powder X-ray diffraction, photoluminescence, thermoluminescence, and Raman spectroscopy studies. The first principles electronic structure elucidation and photoelectrochemical measurements supported a wide bandgap for FeNbO4, in contrast to the narrow bandgap reported previously. Correspondingly, a small photocurrent density was observed for FeNbO4 (similar to 2 to 3 mu A cm(-2)) under 1 sun illumination, suggesting the availability of a smaller cross section of photogenerated charge pairs. Following these band characteristics, while no H-2 evolution was observed, FeNbO4 gave rise to particle size-dependent O-2 evolution during visible light irradiation of water in the presence of electron scavengers, the samples loaded with NiO as cocatalyst showing better activity. Further, the transmission electron microscopy examination revealed the dominant exposure of (011) facets of FeNbO4, besides a significant heterogeneity of inter-domain boundaries. Overall, our results confirm that the photoactivity of metal/oxide nanocomposites is governed by a combination of factors, such as: grain morphology, microstructure, surface adsorption states, and the localized inter-bandgap energy states. Our study also reveals that, in contrast to prevalent assumptions, the wavelength at the absorption edge may not represent the true band-to-band energy gap of metal oxide semiconductors, which is relevant to their photocatalytic activity.